Nest site selection and flying capacity of neotropical wasp Angiopolybia pallens (Hymenoptera: Vespidae) in the Atlantic Rain Forest, Bahia State, Brazil - Da Cruz, Jucelho Dantas; Giannotti, Edilberto [UNESP]; Santos, Gilberto M. M.; Bichara Filho, Carlos C.; Da Rocha, Agda Alves (My University, 2006)
In order to evaluate the flying capacity and nest site selection of Angiopolybia pallens (Lepeletier, 1836), we made 17 incursions (136 hours of sample efforts) in Atlantic Rain Forest environments in Bahia state. Our data show this wasp prefers to nest on wide leaves of bushes and short trees (nests between 0.30 and 3m from the ground) placed in half-shady environments (clearings and shadowed cultivations). The logistic regression model using Quasi-Newton method provided a good description of the flying capacity observed in A. pallens (x 2 = 91.52; p≪0.001). According to the logistic regression model, the A. pallens flight autonomy is low, flying for short distances and with an effective radius of action of about 24m measured from their nests, which means a foraging area of nearly 1,800 m 2.
Keywords: Nest returning; Nesting habits; Social wasp; Angiopolybia pallens; Hymenoptera; Vespidae